EKSTRAKSI BIJI PEPAYA (Carica papaya) SEBAGAI BAHAN AKTIF ANTIBAKTERIAL PADA LARVA UDANG WINDU (Penaeus monodon) SECARA IN VITRO DAN IN VIVO - Cahyadi, Jimmy; Sovina, Laylan (Universitas Borneo Tarakan, 2022)
This research was the administration of papaya seed extract to black tiger prawn which were challenged with Vibrio harveyii infection in vivo and in vitro to determine the effectiveness of papaya seed extract in inhibiting vibrio harveyii. This research was conducted in the laboratory of the Faculty of Fisheries and Marine Sciences, University of Borneo Tarakan in vitro and in vivo. The data obtained were analyzed descriptively and statistically. Based on observations and research it is known that papaya seed extract (Carica papaya) in vitro contains active antibacterial ingredients such as saponins, flavonoids which can inhibit Vibrio in breeding so that it has an impact on the weakness of Vibrio harveyii in disturbing and inhibiting the growth of tiger shrimp larvae during independent research. in vivo. The survival rate of black tiger prawn larvae from the total of each treatment which was maintained for 12 days of treatment showed that the highest value was achieved in treatment P3 of 90% and the lowest was obtained in the negative control treatment of 5%, while in treatment P1 (positive control) of 95 %, P4 was 78% and P2 treatment was 65%.